2015
DOI: 10.1016/s2352-3018(15)00182-4
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting male partners for couple HIV testing and counselling in Malawi's option B+ programme: an unblinded randomised controlled trial

Abstract: Summary Background Couples HIV testing and counselling (CHTC) is encouraged but is not widely done in sub-Saharan Africa. We aimed to compare two strategies for recruiting male partners for CHTC in Malawi’s option B+ prevention of mother-to-child transmission programme: invitation only versus invitation plus tracing and postulated that invitation plus tracing would be more effective. Methods We did an unblinded, randomised, controlled trial assessing uptake of CHTC in the antenatal unit at Bwaila District H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
161
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 157 publications
(188 citation statements)
references
References 20 publications
21
161
5
1
Order By: Relevance
“…Further, a study in Malawi found a similar uptake of partner HIV testing among participants who received invitation cards for their partner (52%) (Rosenberg et al 2015). The similarity in male partner testing levels in the comparison group of our study with those reported in two other studies of the partner invitation approach provide further support for the validity of the measures obtained in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Further, a study in Malawi found a similar uptake of partner HIV testing among participants who received invitation cards for their partner (52%) (Rosenberg et al 2015). The similarity in male partner testing levels in the comparison group of our study with those reported in two other studies of the partner invitation approach provide further support for the validity of the measures obtained in our study.…”
Section: Discussionsupporting
confidence: 84%
“…This is a common limitation in many studies involving HIVST due to the private manner in which self-tests are meant to be used. Despite the potential for self-reporting to be associated with reporting bias, we believe that reporting bias was minimal given the consistency of our results for HIV testing uptake with other studies conducted in SSA (Choko et al 2011;Choko et al 2015;Thirumurthy et al 2016;Rosenberg et al 2015;Osoti et al 2014). In addition, any bias in reporting of HIV testing uptake is unlikely to be differential by study group, thereby maintaining the validity of examining the difference in HIV testing uptake between study groups.…”
Section: Discussionmentioning
confidence: 48%
“…9 Our study suggests that a male partner intervention that is part of a package of PMTCT services and includes a combination of individual, facility-based, and community-based approaches (invitation letters delivered by wives, peer male champions, and male-friendly settings) is acceptable and feasible. The use of invitation letters and tracing to recruit male partners for couple HIV testing and counselling has been effective in option B+ settings, 29 and could prove feasible in our environment when option B+ becomes national policy. Our study also shows that male partners can provide assistance in the use of culturally sensitive and sustainable PMTCT care delivered by lower-cadre providers.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies, such as partner notification and community invitations have been effective for increasing cHCT and could have important implications if brought to scale. [39][40][41] Such efforts would have benefits on reduced HIV incidence and on reaching global HIV targets, including the 90-90-90 goals and elimination of mother-to-child transmission [42][43][44] Assessing the impact of HCT on HIV acquisition is methodologically challenging. First, all assessments of HIV acquisition require large cohorts followed for long periods with low, nondifferential loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%